Diffusion coefficient to mobility ratio in low-dimensional nanostructures - Johari, Zaharah (2009)
The devices are moving towards nanometer domain where modification to it conventional properties need to be made to fit the modification. Diffusion coefficient and mobility are two important parameters to be analyzed as it determine how well particle moves in a semiconductor. New improvement in semiconductors technology have brought to the shrinking of device dimensions from bulk (3-D) to 2-D nanostructures and further reduction of one or more Cartesian direction to nanoscale results in 1-D nanowire. In low dimensional devices the diffusion current cannot be neglected as it does for conventional devices. In degenerate regime, the diffusion coefficient becoming more important as the concentration gradient is emphasized. The degradation of mobility and diffusion coefficient of both nondegenerate and degenerately-doped low dimensional nanostructure with and without quantum emission is elaborated. The Einstein ratio that was established to be equal to the thermal voltage Vt alter in degenerate approximation which shown to be a function of nd depending on it dimensionalities. At higher electric field where quantum emission is present, the ratio is modified by the modulating factor. Present project has obtained extensions for the diffusion coefficient to the degraded mobility for both nondegenerate and degenerately-doped nanostructure with varying dimensionalities subjected to low and high electric field.